Tobramycin and gentamicin-incorporated calcium phosphate beads as delivery system in prevention of Staphylococcus aureus biofilm formation - Che Seman, Che Nor Zarida (2012)
Staphylococcus aureus (S. aureus) is the most common organism causing osteomyelitis which is associated with biofilm formation. This infection is difficult to treat, usually requires prolong administration of antibiotics and extensive surgical procedure. In order to eradicate biofilm formation, biomaterial incorporated with suitable antibiotics can be used as a preventative measure. Therefore, this study was conducted to assess the antibacterial properties of tobramycin and gentamicin-incorporated calcium phosphate beads in prevention of S. aureus biofilm formation. In this present study, the live event for development of S. aureus biofilm was viewed under live cell imaging system and the morphology of biofilm was viewed under scanning electron microscopy (SEM). These microscopic studies showed that the biofilm formation involved initial attachment to a solid surface, the formation of microcolonies,and finally differentiation of microcolonies into exopolysaccharide-encased as matured biofilm. The 3(4, 5-dimethylthiazole-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was used to assess the efficacy of tobramycin and gentamicin-incorporated calcium phosphate beads against S. aureus biofilm. There was a significant difference between tobramycin-incorporated calcium phosphate beads and gentamicin-incorporated calcium phosphate beads on cell viability of S. aureus biofilm (p<0.05). Gentamicin-incorporated calcium phosphate beads showed the strongest action to inhibit S. aureus with IC50 value of 0.05 mg/ml compared to tobramycin-incorporated calcium phosphate beads with IC50 of 0.12 mg/ml. Fluorescence staining with acridine orange and propidium iodide (AOPI) showed that the live bacterial cells appeared green and dead cells appeared red-orange. Ninhydrin assay was used to investigate the elution of tobramycin and gentamicin from the calcium phosphate carrier. The standard graphs for tobramycin and gentamicin solution versus absorbance reading were prepared as references to identify the concentration of the antibiotics release after incorporating calcium phosphate beads at the time points of 0.5 hour, 1 hour, 2 hours, 4 hours, 6 hours, 24 hours, 48 hours, 72 hours, 168 hours (1 week), 336 hours (2 weeks), 672 hours (4 weeks) and 1344 hours (8 weeks). The release of tobramycin from calcium phosphate beads was significantly difference with gentamicin (Fgroup = 175.54 > F0.05, 1, 2 = 18.51). The release of gentamicin from calcium phosphate beads was higher than tobramycin. Futhermore, cumulative release of tobramycin and gentamicin from calcium phosphate beads showed that there was a significant difference in the mean concentration of drug release at 1344 hours (8 weeks) between tobramycin-incorporated calcium phosphate beads and gentamicin-incorporated calcium phosphate beads (p<0.001). The mean cumulative release of gentamicin from calcium phosphate beads (249.3 (2.4) μg/ml) was higher than tobramycin (178.7 (4.1)) at 1344 hours. The cytotoxicity test using MTT assay showed that osteoblast demonstrated good cell viability at the highest concentration of either 25 mg/ml tobramycin or 25 mg/ml gentamicin. There was a significant difference between tobramycin-incorporated calcium phosphate beads and gentamicin-incorporated calcium phosphate beads towards cell viability (p<0.05). Tobramycin-incorporated calcium phosphate beads was more cytotoxic on osteoblast than gentamicin-incorporated calcium phosphate beads. Moreover, investigation on the cell morphology and cell adherence by using SEM and CLSM showed that seeded cells were well attached to the tobramycin and gentamicin-incorporated calcium phosphate beads and continue to grow throughout the 5 days period. In conclusion, tobramycin and gentamicin-incorporated calcium phosphate beads have the potential to be used as a new local drug delivery system in the prevention and treatment of bone infections. Furthermore, tobramycin and gentamicin-incorporated calcium phosphate beads scaffold could serve as a promising platform for the regeneration of osteoid tissues because of their slow release of antibiotic, biocompatibility and biodegradability.